Plasma Insulin Responses to Oral and Intravenous Glucose: Studies in Normal and Diabetic Subjects - Perley, Michael J. (1967)
The plasma insulin responses of normal weight and obese, diabetic, and nondiabetic subjects to intravenous glucose was only 30-40% of that seen after oral glucose, indicating that alimentary mechanism(s) in addition to the arterial blood sugar concentration regulate insulin secretion. Observations made in subjects with diverted portal circulation indicate that the alimentary insulinogenic mechanism is located in the intestinal tract. The insulinogenic potency of the alimentary and glycemic stimuli expressed in terms of insulin secretion per gram of glucose were remarkably similar within each group of individuals. Between these groups, however, there were considerable differences. Obesity, with or without associated diabetes, was associated with a true hypersecretory responsiveness, whereas diabetes was characterized, with or without obesity, by a marked impairment in insulin secretion. The experimental design used in these studies permitted quantitation of the magnitude of the glycemic component of an oral glucose load. As a consequence of impaired insulin secretion, a greater than normal proportion of the oral glucose load escapes initial hepatic extraction in the maturity-onset diabetic and enters the peripheral circulation. Therefore, in the noninsulin-requiring maturity-onset diabetic, the glycemic insulinogenic stimulus for a given oral glucose load is significantly greater than in normal subjects and accounts for the excessive plasma insulin responses observed late in the course of an oral glucose tolerance test.